The Post-Fukushima Protest Cycle and Its Historical Context (KULT_online, 2020)
The first five chapters of Chiavacci and Obinger’s 2018 edited volume study the historical context of the post-Fukushima protest wave. Chapters six to nine examine the 2011-5 protest cycle. Other than two anthropological outliers, the publication relies on historical political sociology and its established branches of social movement theory, civil society studies, and the concept of citizenship. Overall, the book indicates that a new cycle of protest has emerged since 2011, which has tapped into abeyant, older activist networks and an invisible but active civil society.